The Optimal Weight Carriage System for Runners: Comparison Between Handheld Water Bottles, Waist Belts, and Backpacks - Scheer, Volker; Vieluf, Solveig; Bitter, Niko; Christ, Leon; Heitkamp, Hans-Christian (Frontiers in Physiology, 2020)
In endurance running, where fluid and nutritional support is not always readily available, the carriage of water and nutrition is essential. To compare the economy and physiological demands of different carriage systems, 12 recreational runners (mean age 22.8 ± 2.2 years, body mass index 24.5 ± 1.8 kg m−2, VO2max 50.4 ± 5.3 ml kg−1 min−1), completed four running tests, each of 60-min duration at individual running speeds (mean running speed 9.5 ± 1.1 km h−1) on a motorized treadmill, after an initial exercise test. Either no load was carried (control) or loads of 1.0 kg, in a handheld water bottle, waist belt, or backpack. Economy was assessed by means of energy cost (CR), oxygen cost (O2 cost), heart rate (HR), and rate of perceived exertion (RPE). CR [F(2,20) = 37.74, p < 0.01, ηp2 = 0.79], O2 cost [F(2,20) = 37.98, p < 0.01, ηp2 = 0.79], HR [F(2,18) = 165.62, p < 0.01, ηp2 = 0.95], and RPE [F(2,18) = 165.62, p < 0.01, ηp2 = 0.95] increased over time, but no significant differences were found between the systems. Carrying a handheld water bottle, waist belt, or backpack, weighing 1.0 kg, during a 60-min run exhibited similar physiological changes. Runners’ choice may be guided by personal preference in the absence of differences in economy (CR, O2 cost, HR, and RPE).